DNA barcodes of Antipode marine invertebrates in Bay of Biscay and Gulf of Lion ports suggest new biofouling challenges. Issue 1 (December 2018) - Miralles, L.; Ardura, A.; Clusa, L.; Garcia-Vazquez, E.
Abstract Marine biological invasions threaten global biodiversity nowadays. In this article, we have studied fouling communities from 10 port areas of south Bay of Biscay (Atlantic Ocean) and Gulf of Lion (Mediterranean Sea). A total of 834 individuals were genetically barcoded and corresponded to 95 different species. A total of 76 native species 8 genera and 1 family were identified, 58 from the Bay of Biscay and 23 from the Gulf of Lion. Furthermore, 19 species were identified as non-indigenous or cryptogenic (18 from the Bay of Biscay and 4 from the Gulf of Lion). We found a high proportion of Antipode non-indigenous species (NIS) that represented the 19.3% of all sampled individuals and the 54.21% of NIS specimens of this study. A framework for inference of donor regions based on a phylogenetic screening of genetic sequences was proposed as a proof of concept and tested, as well as models for the relationship between NIS introductions, maritime imports and distance to NIS native range and inferred donor areas. Consistent generalized linear models (GLM) with positive association between NIS genetic diversity and distance, not with maritime growth weight imports, strongly suggest that distant NIS could pose higher invasion risk than closer species. Selection for wider tolerance ranges during the long travel –direct or stepwise, as well as environmental similarity between donor and receiving regions, may explain these results.